User Consideration About Dwelling and Its Environment Trabzon- Turkey TOKİ Dwelling Sample - İslamoğlu, Özge; USTA, GÜLAY (My University, 2014)
The migrations since 1950, has been revealed dwelling problem more seen in big cities. To solve this revealed dwelling problem, housing application has been started by Emlak Bank since 1960. However, because of finadequate financing fundings, private companies and building companies couldn’t be sufficient. By occuring budgetary and extrabudgetary sources in 1980, housing applications has been accelerated. Today in large part of housing application is realising by TOKI. Made quickly in these applications to solvingin housing problem, prioritising maxim of quantity, In terms of the quality of the negativity of the opinion that it is quite common. In this study extensively in all cities located within housing production practices TOKI, has been the subject of evaluation on users. That have been applied in the city of Trabzon in two separate regions of residents who live in public housing, housing and the environment to reveal the satisfaction of statistical analysis were used. The objective here before quantitative targets, for users to evaluate the quality of life, the emphasis is to make.
Keywords: Konut; kullanıcı gereksinimleri; Housing Estate; Dwelling; TOKI; Consumer Satisfaction